Washing Test: with or without involvement of chloroform & aceton - Sedijani, Prapti; Muhidayani, RE Septi; Kusmiyati, Kusmiyati; Sukarso, AA (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Chloroform and aceton are commonly used in washing test, while both are unfriendly to human health. This research is aimed to evaluate if those chemicals are really needed foe such purpose by seeing the washing power with or without those chemicals. There are four conditions of washing test: Involving both as usual (CA); chloroform only (C); chloroform and ethanol instead (CE); and None of both (OO). Washing test was carryout within a 0% and 1% of detergent. Two Way ANOVA Statistical analysis revealed that there was a very significant differences among the treatments, and Duncan analysis showed that with or without chloroform and aceton resulting in the same category of washing power, except the CE treatment resulted in a lower washing power. Hence there is a choice weather chloroform and aceton be involved in the procedure.